Co-Supplementation of Flos Sophorae Extract with Tremella fuciformis Polysaccharides Improves Physicochemical, Textural, Rheological, and Antioxidant Properties of Low-Fat Yogurts - Renyong Tang; Yurong Lu; Caiyun Hou; Jiaxuan Peng; Wei Wang; Xiulan Guo (Journal of Food Quality)
Flos Sophorae extract (FSE) with abundant rutin and Tremella fuciformis polysaccharides (TP) could act as novel natural improvers of low-fat yogurt due to their health benefits and properties of interacting with proteins. This study attempted to understand how FSE or its combination with TP influences physicochemical, textural, and antioxidant properties of low-fat yogurts. The results indicated that the low concentrations of FSE (1.2 or 2.4%) increased the antioxidant activity, prompted the S. thermophilus growth, water holding capacity (WHC), and textural and sensory properties, and shortened the fermentation time, but reduced the rheological properties of yogurts compared with the control. Co-supplementing appropriate TP with the optimum FSE concentration (2.4%) improved the rheological properties, and further enhanced the S. thermophilus growth, WHC, textural and antioxidant properties, and sensory scores of yogurts compared with the 2.4% FSE group, with the best effects at 0.4 mg/mL TP. Taken together, co-supplementation of polyphenols extract FSE with Tremella fuciformis polysaccharides may be an available strategy to optimize health-promoting properties and overcome defects of low-fat yogurts.